الأبعاد الدلالية في قصيدة في القدس للشاعر تميم البرغوثي - برتيمة، دنيا, بوقرة، سعاد; بن فرحات، سميحة (University of El-oued, 2022)
يعتبر الإنسان هو الكائن الوحيد الذي يسعى للوصول الى المعرفة إذ لا تتحقق هذه الغاية إلا باللغة ولا يتم ذلك إلا بالاتصال مع بني جنسه ولا تبرز قيمة اللغة إلا باتصالها بالمعنى. لقد تناول هذا البحث دراسة الأبعاد الدلالية في قصيدة "في القدس" للشاعر تميم البرغوثي, إذ يعتبر علم الدلالة علم فسيح المجالات, نظرا لاتصاله بالعلوم اللغوية المختلفة, وقد حاولنا بجهد الجهيد البحث في الأفكار التي تعرض لها العلماء العرب القدامى والمحدثين العرب والغرب في هذا الميدان وكما تطرقنا إلى الإشارة إلى بعض النظريات الحديثة في الدرس اللساني، كان هذا ما تناولناه في الجزء النظري أما الجانب التطبيقي فقد حاولنا فيه دراسة الأبعاد الدلالية في قصيدة "في القدس" للشاعر تميم البرغوثي واستخراج أهم الأبعاد المستخدمة فيها منها "البعد الدلالي للمكان, للزمان, للشخوص, للذين, للتاريخ, للألم والغياب, للأمل والتفاؤل , وختمنا بحثنا بخاتمة كانت حوصلة للموضوع إضافة الى الملحق الذي يخص الشاعر وقصيدته . Notebook summary: Man is considered the only being who seeks to reach knowledge, as this goal is not achieved except by language, and this is only accomplished by contacting his species, and the value of language does not emerge except through its connection with meaning. This research dealt with the study of the semantic dimensions in the poem “In Jerusalem” by the poet Tamim Barghouti, as semantics is considered a broad science, due to its connection with various linguistic sciences, and we have tried hard to research the ideas that the ancient Arab scholars and modern Arabs and the West were exposed to in this field. As we touched on the reference to some modern theories in the linguistic lesson, this was what we dealt with in the theoretical part. As for the practical side, we tried to study the semantic dimensions in the poem “In Jerusalem” by the poet Tamim Barghouti and extract the most important dimensions used in them, including “the semantic dimension of place, time, For people, for those, for history, for pain and absence, for hope and optimism, and we concluded our research with a conclusion that was a summary of the subject in addition to the appendix that pertains to the poet and his poem.
Keywords: الجهود الدلالية عند العرب القدامى- الأبعاد الدلالية –تميم البرغوثي- النظريات الحديثة في الدرس اللساني; The Semantic Efforts of the Ancient Arabs - Semantic Dimensions - Tamim Barghouti - Modern Theories in the Linguistic Lesson